2020
DOI: 10.1038/s41598-020-73739-0
|View full text |Cite
|
Sign up to set email alerts
|

Continental-scale patterns of hyper-cryptic diversity within the freshwater model taxon Gammarus fossarum (Crustacea, Amphipoda)

Abstract: Traditional morphological diagnoses of taxonomic status remain widely used while an increasing number of studies show that one morphospecies might hide cryptic diversity, i.e. lineages with unexpectedly high molecular divergence. This hidden diversity can reach even tens of lineages, i.e. hyper cryptic diversity. Even well-studied model-organisms may exhibit overlooked cryptic diversity. Such is the case of the freshwater crustacean amphipod model taxon Gammarus fossarum. It is extensively used in both applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 115 publications
1
67
0
Order By: Relevance
“…Freshwater sentinel species Gammarus fossarum is one of the most represented amphipod crustaceans widespread across European inland aquatic habitats ( Wattier, et al., 2020 ). Its broad distribution and sensitivity to a wide range of contaminants has made this keystone species a valuable model organism in ecotoxicology ( Besse, et al., 2013 ; Chaumot, et al., 2015 ; Dedourge-Geffard, et al., 2009 ; Kunz, et al., 2010 ; Mehennaoui, et al., 2016 ; Wigh, et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Freshwater sentinel species Gammarus fossarum is one of the most represented amphipod crustaceans widespread across European inland aquatic habitats ( Wattier, et al., 2020 ). Its broad distribution and sensitivity to a wide range of contaminants has made this keystone species a valuable model organism in ecotoxicology ( Besse, et al., 2013 ; Chaumot, et al., 2015 ; Dedourge-Geffard, et al., 2009 ; Kunz, et al., 2010 ; Mehennaoui, et al., 2016 ; Wigh, et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This area is known to be a biodiversity hotspot with high level of endemism ( Médail and Diadema, 2009 ). This is also the case for many endemic freshwater gammarids ( Grabowski et al, 2017 ; Csapó et al, 2020 ; Wattier et al, 2020 ). Within the G. balcanicus morphospecies, at least 50 divergent MOTUs (Molecular Operational Taxonomic Units) have been identified ( Mamos et al, 2016 ), most of them being locally endemic, dating back even to 15 Mya.…”
Section: Introductionmentioning
confidence: 71%
“…The biogeography of the Western Palearctic was proven to be more complex than the classical theory of the three Mediterranean glacial refugia, as the genetic analysis of several different groups supported the presence of many extra-Mediterranean refugia throughout Europe (Schmitt & Varga, 2012; Wattier et al ., 2020). Studies focusing on the Danube catchment identified the Ponto-Caspian Region and the Pannonian Basin as extra-Mediterranean refugia areas for many vertebrate and invertebrate taxa (Bănăduc et al ., 2016; Vörös et al ., 2016; Csapó et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%